2018
DOI: 10.1051/matecconf/201824700016
|View full text |Cite
|
Sign up to set email alerts
|

Children exposure to PM2.5 in kindergarten classrooms equipped with air purifiers - a pilot study

Abstract: Children exposure to PM 2.5 is associated with several negative health effects. Particulate air pollution in the ambient and indoor air could lead to exacerbation of respiratory diseases and even influence cognitive function in children. One of the methods to improve indoor air quality is to use electronic air purifiers. Such an equipment is still not commonly used in Polish kindergartens and homes. The aim of the study was to assess changes in children exposure to particulate air pollution in kindergarten cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 4 publications
(1 reference statement)
1
6
0
Order By: Relevance
“…The removal efficiency of bioaerosols in Seoul, Korea, was 41-68% for CBA [23]. Similar studies conducted in Poland indicate that the effectiveness of purifiers in kindergartens was 41% [46]. It seems that the use of an AP may be considered in cases where natural ventilation is used, but there are concerns related to indoor pollution from external sources, or if the ventilation system is not effective at removing particles.…”
Section: The Concentration Of Cbamentioning
confidence: 66%
“…The removal efficiency of bioaerosols in Seoul, Korea, was 41-68% for CBA [23]. Similar studies conducted in Poland indicate that the effectiveness of purifiers in kindergartens was 41% [46]. It seems that the use of an AP may be considered in cases where natural ventilation is used, but there are concerns related to indoor pollution from external sources, or if the ventilation system is not effective at removing particles.…”
Section: The Concentration Of Cbamentioning
confidence: 66%
“…In our previous study conducted in Polish dwellings, the concentration of bacterial aerosols was reduced by almost 50% when APs were enabled (Bragoszewska et al, 2019). Similar studies conducted in Poland indicate that the effectiveness of APs for the reduction of particulate matter (PM) in kindergartens was 41% (Gayer et al, 2018). Previously conducted studies have shown that HEPA filters can reduce particle number concentrations by more than 50% (Batterman et al, 2012;Wheeler et al, 2014;Kelly and Fussell, 2015).…”
Section: Resultsmentioning
confidence: 83%
“…The average level of bacterial aerosol concentration in the indoor air exceeded almost threefold the average level recorded in the outdoor air (401 CFU/m 3 ). The ratio values of indoor to outdoor bacteria numbers (I/O bacteria) are generally used as an identifier for emission sources of bioaerosols (Nasir and Colbeck, 2010;Gayer et al, 2018). If this ratio is >1.0, there is a difference between outdoor and indoor biological aerosol sources and the source exists in the indoor space (Brągoszewska et al, 2018b).…”
Section: Resultsmentioning
confidence: 99%
“…While portable air cleaners are commonly used to reduce PM concentrations, especially in locations near roadways and other sources of air pollution, less is known about the use of conventional fans. Several studies have tested the use of portable air cleaners in school settings, characterizing their effectiveness in reducing exposure to PM 2.5 alone [19]; PM 10 alone [17]; PM 2.5 and PM 10 [12,20]; airborne allergens [21]; ultrafine particles (UFPs), black carbon, PM 2.5 and PM 10 , and volatile organic compounds (VOCs) [16]; as well as their effect on indoor NO 2 and CO 2 concentrations [22]. Only one study has evaluated the performance of fans in mitigating PM levels in classrooms [23].…”
Section: Introductionmentioning
confidence: 99%